Extraction of djenkolic acid from pithecellobium jiringan seeds using supercritical carbon dioxide extraction - Che Yunus, Mohd. Azizi (2006)
Djenkolic acid (or sometimes jengkolic acid) is a sulfur-containing non-protein amino acid naturally found in djenkol beans of the South-East Asian legumes jengkol (Archidendron jiringa). The toxin consists of two cysteine radicals connected by a single carbon between the sulfur atoms. It is toxic to humans, often causing kidney failure.